دور الاسواق المالية في جذب الاستثمارات الاجنبية - عبد الكريم, توفيق (جامعة محمد بوضياف المسيلة, 2015)
Recently, many countries are moving toward markets economies by many tools and methods that ensure the provision of funds for economic development, so I resorted to activate the money market and the creation of new methods and tools for investment, which fit with the local environment and the growth of the local economy and its requirements. The stock market is the base of money markets because it realizes the liquidity and diversification of risk, as well and the good management of companies. They offer different investment tools which the share and the stock are the most important, the Investor depends in the banknote about the informations of the banknote to take the decision of investment without it, the studying of the financial market helps, through various analysis types, to reinforce the investor decisions